2012
DOI: 10.1093/nar/gks742
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori oriC —the first bipartite origin of chromosome replication in Gram-negative bacteria

Abstract: Binding of the DnaA protein to oriC leads to DNA melting within the DNA unwinding element (DUE) and initiates replication of the bacterial chromosome. Helicobacter pylori oriC was previously identified as a region localized upstream of dnaA and containing a cluster of DnaA boxes bound by DnaA protein with a high affinity. However, no unwinding within the oriC sequence has been detected. Comprehensive in silico analysis presented in this work allowed us to identify an additional region (oriC2), separated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(110 citation statements)
references
References 69 publications
4
105
1
Order By: Relevance
“…Two oriC subregions, oriC1 and oriC2, were recently identified flanking the dnaA gene in Helicobacter pylori. The DnaA box sequences of oriC1 and oriC2 are oriented in the same direction, and it is suggested that the DnaAoriC1 subcomplex interacts with the DnaA-oriC2 subcomplex via DNA looping of the dnaA gene region (61,62). In the resultant complex, the directions of the DnaA complexes formed at oriC1 and oriC2 would then be opposed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two oriC subregions, oriC1 and oriC2, were recently identified flanking the dnaA gene in Helicobacter pylori. The DnaA box sequences of oriC1 and oriC2 are oriented in the same direction, and it is suggested that the DnaAoriC1 subcomplex interacts with the DnaA-oriC2 subcomplex via DNA looping of the dnaA gene region (61,62). In the resultant complex, the directions of the DnaA complexes formed at oriC1 and oriC2 would then be opposed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The H. pylori replication origin, HporiC, has also been identified in the H. pylori chromosome. The initiator protein HpDnaA binds to the unique bipartite replication origin HporiC and initiates DNA unwinding in vitro (14). Recently, a unique DnaA binding protein, HobA, has been identified as the regulator of the timing and frequency of DnaAdependent initiation from oriC by aiding the oligomerization of DnaA for orisome (a multiprotein complex formed at the oriC) assembly at HporiC, analogous to DiaA function in Escherichia coli (15).…”
mentioning
confidence: 99%
“…A 500-bp DNA fragment containing a putative HporiC region was PCR amplified from H. pylori 26695 genomic DNA using forward and reverse primers (HporiCFw, 5= GGCGTTATTATAGCGTG AATA 3=, and HporiCRv, 5=CATTTTTTTAGCGAACATTTC3=, respectively). These primers were designed to amplify the 500-bp region of the chromosome upstream of the DnaA box sequences containing the putative HporiC (14). The purified PCR product was prepared as a probe using a fluorescence in situ hybridization multicolor kit with Alexa Fluor 594 dye or Alexa Fluor 488 dye (Invitrogen Inc., USA), following the manufacturer's instructions.…”
mentioning
confidence: 99%
“…Several DNA replication proteins, such as the initiator proteins DnaA and Hob-A (31-34), the replicative helicase DnaB and its unique dodecameric architecture (35)(36)(37)(38), and the single-stranded DNA-binding protein (SSB) (39), have been characterized in H. pylori. Recently, first bipartite origin of chromosome replication in Gram-negative bacteria was reported in H. pylori (40). HpDnaB is unique because it can bypass the EcDnaC function in vivo, suggesting that it has an independent helicase loader function (41).…”
mentioning
confidence: 99%